EFL LEARNERS PERCEPTION IN VOCABULARY ACQUISITION USING ENGLISH NOVELS - Anggita, Windy Ayu; Rosnija, Eni; Rezeki, Yanti Sri; Bunau, Eusabinus; Rahmani, Eka Fajar (Universitas Tanjungpura, 2023)
This research investigates EFL learners